READINESS AND COMPETENCE OF SENIOR HIGH SCHOOL ENGLISH TEACHERS TO IMPLEMENT CURRICULUM 2013 - Sundayana, Wachyu (Universitas Pendidikan Indonesia, 2015)
The implementation of curriculum is considered as one of the most prominent phases in developing 2013 primary and secondary curriculum in Indonesia, and this is greatly influenced by teachers’ readiness and competence. This research aims to investigate teachers’ readiness and competence to implement the 2013 Curriculum, particularly viewed from their comprehension about the syllabus of English subject and its development into lesson plans based on the principles of syllabus development as suggested in the curriculum, as well as their ability and their self-efficacy in implementing the curriculum in classroom teaching and learning processes. Twelve senior high school teachers from different schools were assigned to complete a questionnaire about their readiness and competence to implement the 2013 curriculum and were observed in their teaching and learning process. Both quantitative and qualitative analysis were employed in the research. Results from quantitative analysis showed that teachers’ readiness to implement the curriculum had low correlation on their competence. Qualitative analysis revealed that teachers had adequate readiness to implement the curriculum and competence to develop lesson planning. For further studies, studies on the aspects of teachers’ attitude, motivation, belief, and commitment to implement the 2013 curriculum need to be further investigated.